2021
DOI: 10.3390/ani11040961
|View full text |Cite
|
Sign up to set email alerts
|

Grumpy Dogs Are Smart Learners—The Association between Dog–Owner Relationship and Dogs’ Performance in a Social Learning Task

Abstract: We investigated how dog–owner relationship–with a focus on possible behavioural problems–might associate with the individual variability in dogs’ social learning performance. Dog owners first completed a questionnaire about their relationship with their dogs (N = 98). Then, dogs were tested in a detour test: a control group without demonstration, a group where the owner demonstrated the task and another group where the experimenter demonstrated the task. Finally, the dogs participated in two behaviour tests me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…We found that individuals that exhibited more reaching behaviours were also more successful in solving the task. Likewise, more persistent and goal-orientated dogs were more successful in a detour task (Pongrácz et al, 2021). Interestingly, this reaching behaviour was not equally related to success across the three test groups.…”
Section: Discussionmentioning
confidence: 88%
“…We found that individuals that exhibited more reaching behaviours were also more successful in solving the task. Likewise, more persistent and goal-orientated dogs were more successful in a detour task (Pongrácz et al, 2021). Interestingly, this reaching behaviour was not equally related to success across the three test groups.…”
Section: Discussionmentioning
confidence: 88%
“…And indeed, we found that llamas that were more distracted and less focused on the food were also less successful. Only attentive individuals can extract information from demonstrations (Range and Huber 2007 ) but also persistence and goal-orientation can facilitate success (Pongrácz et al 2021 ). Interestingly, distraction behaviours and food-related behaviours differed between test groups.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this theory, one study has found no difference among several dog breeds’ performance in the detour task after observing human demonstration [ 31 ]. However, we found that the social dynamics in dogs’ environments (such as their position in conspecific hierarchy [ 32 ], dog–owner interactions [ 33 ] and potentially the interaction between the environment and inherited temperament factors (personality)), could influence dogs’ social learning performance [ 34 ]. According to the results of the aforementioned studies, high-ranking dogs from multi-dog households show better social learning performance than lower-ranking individuals in case of a human demonstrator; however, lower-ranking dogs learn much better from a dog demonstrator than high-ranking dogs do [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of the aforementioned studies, high-ranking dogs from multi-dog households show better social learning performance than lower-ranking individuals in case of a human demonstrator; however, lower-ranking dogs learn much better from a dog demonstrator than high-ranking dogs do [ 32 ]. Additionally, those dogs that behave assertively and show a stronger tendency to be aggressive with their owner performed better in the detour task where an unfamiliar experimenter demonstrated the task [ 33 ]. Finally, we have found that the personality traits that are associated with being more dominant in the hierarchy could also enhance dogs’ responsiveness to social stimuli in a learning context [ 34 ].…”
Section: Introductionmentioning
confidence: 99%